Peningkatan Berpikir Kritis Siswa Dengan Model Pembelajaran Problem Based Learning - Meriyanti Weni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
The purpose of this study was (1) to find out the application of the problem-based Learning Learning model to improve critical thinking skills and (2) to find out the improvement of student critical thinking skills through the application of the problem-based learning model to improve students thinking skills critical of class X IPS SMA PGRI Swasthika Lewolebe. This type of research was classroom action research (PTK), intended to improve classroom learning. The subjects of this study were students of grade X IPS SMA PGRI Swasthika Lewoleba, with 24 students. The method used in this study was a test. The research data were analyzed using quantitative analysis data. The study results can conclude that problem-based learning models can increase students' critical thinking skills at SMA PGRI Swasthika Lewoleba. Think can be proven by improving student learning outcomes in each cycle; it was very good, with a percentage of 29.16 % in the category good; in the first cycle, the rate increased to 37.5% in the good category, and in the second cycle it was very good with a percentage of 95.8% in the very good category. These results have achieved the success criteria set by the researcher, namely 80% above KKM 75.